Prevention of Terrorism Act (PTA) : a critical analysis - Bastiampillai, Bertram; Bastiampillai, Bertram; Edirisinghe, Rohan; Kandasamy, N.; Centre for Human Rights and Development (Colombo, Sri Lanka) (Colombo : Centre for Human Rights and Development, 2009)
Contributed articles.
Keywords: Terrorism -- Sri Lanka; Terrorism -- Sri Lanka -- Prevention; Civil rights -- Sri Lanka